2016
DOI: 10.4103/0976-500x.195898
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension influences the exponential progression of inflammation and oxidative stress in streptozotocin-induced diabetic kidney

Abstract: Objective:To investigate the association of hypertension coexisting with diabetes mellitus with oxidative stress and inflammation in the kidneys of streptozotocin (STZ)-induced diabetic rats.Materials and Methods:Male Wistar rats were used for the experiments. Blood glucose (BG), urea, blood pressure (BP), and heart rate (HR) were analyzed before and 48 h after STZ injection. Further, these parameters were monitored up to 3 months of diabetes induction. Subsequently, the inflammatory markers (C-reactive protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Upregulation of Trpc1 may be a consequence of hemodynamic disturbances in the diabetic heart which in turn stimulates mechano-sensitive TRPC channels thereby providing an alternative entry pathway for Ca 2+ in the face of depressed L-type Ca 2+ current in AVN cells and reduced heart rate in STZ-induced diabetic heart ( 32 , 33 ). Previous studies have reported elevation of mean arterial pressure in STZ-induced diabetic rats which may in turn lead to hypertrophy of the heart which would be consistent with the increase in heart weight to body weight ratio, which in turn might elicit an effect on the mechano-sensitive channels ( 53 ).…”
Section: Discussionsupporting
confidence: 55%
“…Upregulation of Trpc1 may be a consequence of hemodynamic disturbances in the diabetic heart which in turn stimulates mechano-sensitive TRPC channels thereby providing an alternative entry pathway for Ca 2+ in the face of depressed L-type Ca 2+ current in AVN cells and reduced heart rate in STZ-induced diabetic heart ( 32 , 33 ). Previous studies have reported elevation of mean arterial pressure in STZ-induced diabetic rats which may in turn lead to hypertrophy of the heart which would be consistent with the increase in heart weight to body weight ratio, which in turn might elicit an effect on the mechano-sensitive channels ( 53 ).…”
Section: Discussionsupporting
confidence: 55%
“…In the present study, the administration of STZ showed significant hyperglycemia, hypoinsulinemia, and significant oxidative stress with a marked increase in the levels of HbA1c, AGEs, cholesterol, TG, LDL, total lipids, urea, uric acid, creatinine, AST, ALT, ALP, bilirubin, CPK, and inflammatory markers including IL-6, TNF- α , and CRP, while C-peptide, HO-1, HDL, albumin, and amylase and growth factors like liver and serum IGF-1 levels markedly decreased. A variety of studies have demonstrated parallel results [ 26 29 ].…”
Section: Discussionmentioning
confidence: 92%
“…Oxidative stress is essential in the development of injury following CIRI [6] and these effects are known to be exacerbated in patients with diabetes [7]. Additionally, the inflammation induced by CIRI is significantly enhanced in patients with diabetes [8]. An in vitro study also found that high glucose induces ROS production and activates cytokine secretion [9].…”
Section: Introductionmentioning
confidence: 86%